Bagaimana Sistem Informasi Mengubah Bisnis? Dampak Bagi Usaha Mikro Kecil Dan Menengah - Tio Sinta Marito Br. Marbun; Zahwa Juwita (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The very rapid development of information systems has made business no longer a difficult thing to do. Now everything can be done more easily with information systems and technological advances. Every business or business uses information systems to increase competitiveness and the quality of the products produced. As technology and information systems develop, MSMEs are expected to be able to compete. The research method used is the descriptive method, namely a research method that describes the situation or circumstances of the object being researched to obtain accurate and factual information. The results of this research, show that information systems have a very important role in business, especially in the development of MSMEs. Information systems provide great opportunities for MSMEs to continue to develop and enter the global market. Suggestions are expected to be able to follow developments in information systems so as not to lose competitiveness. Has recognized product quality and reaches a wide market. MSMEs will continue to progress and grow if they are able to follow the flow of globalization through the development of information systems.